The Fiscal Consequences of Shrinking Populations - Clements, Benedict (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
This Staff Discussion Note looks at the stark fiscal challenges posed by the decline and aging of populations between now and 2100. It finds that without reforms, pensions and health spending would rise to 25 percent of GDP by end-century in more developed countries (and 16 percent of GDP in less developed countries), with potentially dire fiscal consequences. Given the uncertainty underlying the population projections and associated large fiscal risks, a multi-pronged approach will be required. This could include entitlement reform-starting now but at a gradual pace; policies that affect demographics and labor markets; and better tax systems and more efficient public expenditure.